2019
DOI: 10.1007/s10654-019-00519-0
|View full text |Cite
|
Sign up to set email alerts
|

Early imaging biomarkers of lung cancer, COPD and coronary artery disease in the general population: rationale and design of the ImaLife (Imaging in Lifelines) Study

Abstract: Lung cancer, chronic obstructive pulmonary disease (COPD), and coronary artery disease (CAD) are expected to cause most deaths by 2050. State-of-the-art computed tomography (CT) allows early detection of lung cancer and simultaneous evaluation of imaging biomarkers for the early stages of COPD, based on pulmonary density and bronchial wall thickness, and of CAD, based on the coronary artery calcium score (CACS), at low radiation dose. To determine cutoff values for positive tests for elevated risk and presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 50 publications
0
41
0
Order By: Relevance
“…The ImaLife study is an ongoing study embedded in the Lifelines cohort, 17 which was designed to establish reference values of imaging biomarkers for early stages of the big three diseases: CAD, lung cancer, and chronic obstructive pulmonary disease. 18 In brief, the Lifelines cohort was launched in 2006 (baseline round) to collect data from physical examinations; laboratory tests; and questionnaires on general demographics, health status, lifestyle, and environmental factors. Generally, every 1.5 years, follow-up questionnaires on aforementioned aspects were administered, and every 5 years, follow-up assessments were scheduled for renewed physical examinations and laboratory tests.…”
Section: Methodsmentioning
confidence: 99%
“…The ImaLife study is an ongoing study embedded in the Lifelines cohort, 17 which was designed to establish reference values of imaging biomarkers for early stages of the big three diseases: CAD, lung cancer, and chronic obstructive pulmonary disease. 18 In brief, the Lifelines cohort was launched in 2006 (baseline round) to collect data from physical examinations; laboratory tests; and questionnaires on general demographics, health status, lifestyle, and environmental factors. Generally, every 1.5 years, follow-up questionnaires on aforementioned aspects were administered, and every 5 years, follow-up assessments were scheduled for renewed physical examinations and laboratory tests.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset consisted of scans (a minimum of 300 slices per scan) reconstructed in the axial plane with filtered back projection using the Br40 kernel (qualitative-smooth). The acquisition protocol for the dataset has been previously published [36]. The detailed consort of dataset used in the study is provided in the Fig.…”
Section: A Data Descriptionmentioning
confidence: 99%
“…The external validation dataset was collected from the ImaLife study [11]. The ImaLife study is an embedded study of the Lifelines cohort [12], which was designed to establish references values of imaging biomarkers in the Dutch population for the early stage of the big three diseases : lung cancer, chronic obstructive pulmonary disease and coronary artery disease.…”
Section: Study Populationmentioning
confidence: 99%
“…The complete scan protocols and designs of the used studies can be found in the design papers of ROBINSCA [9] and ImaLife [11]. We will mention the main differences between the two.…”
Section: Scan Protocolsmentioning
confidence: 99%